Let $X$ be positive random variable and its distribution is symmetric about its mean value $m$. Then $$ E\left[\frac{1}{X}\right] \geq \frac{1}{m} + \frac{\sigma^2}{m^3}, $$ where $\sigma^2$ is variance of $X$. I can just prove that $$ E\left[\frac{1}{X}\right] \geq \frac{1}{m}, $$ using Jensen, but somehow can't incorporate symmetry and get also the second term.

  • 1
    $\begingroup$ Do you have a reference for that inequality? Well, probably not ... a positive random variable can be symmetric only if it is bounded, so you can as well assume boundedness too. $\endgroup$ – kjetil b halvorsen Feb 4 '18 at 13:14
  • $\begingroup$ Unfortunately not, but it is obvious that $X\leq2m,$ but still how to incorporate variance? $\endgroup$ – Ethan Feb 4 '18 at 14:10

Let's try the usual preliminaries: simplify by choosing appropriate units of measurement and exploiting the symmetry assumption.

Reframing the question

Change the units of $X$ so that its mean is $m=1$: this will not alter the truth of the inequality. Thus the distribution $F$ of $X$ is symmetric about $1$ and the range of $X$ is within the interval $[0,2]$. Our objective is to prove

$$\int_0^2 \frac{1}{x}dF(x) = E\left[\frac{1}{X}\right] \ge 1 + \sigma^2 = E[X^2] = \int_0^2 x^2 dF(x).$$

Since $dF$ is invariant under the symmetry $x\to 2-x$, break each integral into two integrals over the intervals $[0,1)$ and $(1,2]$ and change the variable from $x$ to $2-x$ over the second interval. We may ignore any probability concentrated at the value $1$ because at that point $1/x = x^2.$ Whence the problem reduces to demonstrating

$$\int_0^1 \left[\left(\frac{1}{x} + \frac{1}{2-x}\right) -(x^2 + (2-x)^2)\right]dF(x) \ge 0.\tag{*}$$

This can happen only if the integrand

$$g(x) = \frac{1}{x} + \frac{1}{2-x} -(x^2 + (2-x)^2)$$

is nonnegative on the interval $(0,1].$ That's what we must show.


You could apply differential calculus. Elementary demonstrations are also available. When $0 \le x \le 1$, it will be the case that $0 \le |x-1| \le 1$, whence $1 \le 1/|x-1|$, entailing

$$1 \le \frac{1}{(x-1)^2} \le \frac{1}{(x-1)^4}.$$

This implies

$$0 \le \frac{1}{(x-1)^4} - \frac{1}{(x-1)^2} = \frac{2}{g(x)},$$

showing $g(x) \ge 0$ for $x\in (0,1],$ QED.

The inequality is tight in the sense that when $F$ concentrates its probability closer to $1$, the inequality gets closer to being an equality. Thus, we could not replace $\sigma^2/m^3$ in the original inequality by any multiple $\lambda\sigma^2/m^3$ with $\lambda \gt 1$.

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.